Analysis of outcome of dorsal onlay urethroplasty using buccal mucosal graft and vaginal wall graft for female urethral stricture - Gaurav Babelay; Ahsan Ahmad; Nikhil Ranjan; Kumar Dheeraj (Urology Annals)
Background: It was estimated that 3%–8% of women presented with bladder obstruction, and 4%–13% of these women had female urethral stricture (FUS), which is an uncommon disorder. Aims: The study has been conducted to analyze the outcome of Dorsal onlay urethroplasty using buccal mucosal graft (BMG) and vaginal wall graft (VWG) for FUS. Settings and Design: It was a retrospective, single-centric cohort study. The study has been conducted for 2 years and 2 months, i.e., from July 2021 to September 2023. Subjects and Methods: The study included 20 female patients with urethral stricture who had urethroplasty. The participants were further classified into two groups respectively. One of the groups included 10 participants with cases of BMG urethroplasty and another 10 were cases of VWG urethroplasty. Statistical Analysis: The Statistical Package for the Social Sciences (SPSS) version 24 program was used to analyze the data. Both continuous and categorical variables were present in the data. Descriptive Statistics were expressed as mean ± standard deviation or n (%) or n. Results: The BMG group had a substantially lower postvoid residual (PVR) of 10 ± 4.2 mL than the VWG group, which had a PVR of 15 ± 6.4 mL with a P = 0.04. The operating time was 110 ± 10.8 in the BMG urethroplasty group and 90 ± 8.2 in the VWG group with a P < 0.001. VWG urethroplasty group. No statistically significant differences were observed in terms of AUA symptom score and Qmax. Conclusion: The study concluded that FUS reconstruction can offer a good, long-lasting response. Moreover, between both the preferred techniques of BMG and VWG urethroplasty, which is safe and effective, patients with postmenopausal atrophy or vaginal pathology may benefit more from BMG.